THE RECRUITMENT OF THE CIVIL STATE CIVIL APPARATUS ON THE BODY OF THE KEPEGAWAIAN AREA OF THE CITY OF MANADO - GAGOLA, JIMY; LENGKONG, FLORENCE; TULUSAN, FEMMY (Sam Ratulangi University, 2019)
This study aims to determine the recruitment of the civil state apparatus at the regional employment board thecity of manado, this research use apporoach qualitative description, the author rate is based on the recruitmentprocces with the data collected through interview techniques, observation, and dicumen of 5 informants yerkaitdirectly with the implementation of the recruitment process of the civil state apparatus in the employmentagency topography of the city of manado, based on research do then known there is good communication andclear abaot the process recruitment employees in the employment agency area of the city manado theavailability of resources thant support such as human resources and infrastructure in the recruitment ofemployees, the level of honesty and commitment the employee-owned quite good. Not convoluted like theprocess of recruitment is done online to anticipate the collection of wild, felt already better, in terms oftransparency and akuntabilitasi in the process of recruitment has been very good but there are still some thingsthat need to be improved again for the fix kualitad existing employeesKey Word : Rekruitment Of The State Civil Apparatus Staffing